Pendampingan Digitalisasi Pemasaran dan Penguatan Branding bagi UMKM Sarung Tenun di Kabupaten Mamuju - Eka Wahyuliana; Ansar; Nur Jaya Baiduri Ruslan; Suhartini (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2025)
Mamuju Regency holds significant potential in the creative economy sector, particularly through traditional woven sarong crafts managed by women artisans. However, limited digital literacy and a lack of understanding in business management—especially in branding and online marketing—pose major challenges to the development of these enterprises. This community service program aims to enhance the capacity of local artisans by providing training in branding management and the utilization of e-commerce platforms. The activities include interactive workshops, brand identity development, product photography techniques, effective product description writing, and mentoring in the use of social media and online marketplaces such as Shopee and TikTok Shop. The results of the program show a significant increase in participants’ understanding of brand image importance and digital marketing strategies. Several participants successfully applied the training outcomes by creating business accounts and starting to sell their products online. This program is expected to serve as a sustainable model for empowering local creative economies based on cultural heritage.